Lattice Boltzmann and Finite Volume Simulation of Inviscid Compressible Flows with Curved Boundary (Advances in Applied Mathematics and Mechanics, 2021)
A 2D lattice Boltzmann model for inviscid compressible flows was proposed in this paper.Finite volume method was implemented on 2D curvilinear structural grids to solve thelattice BGK-Boltzmann equations. MUSCL scheme was used to perform interpolation.The obtained results agree excellently well with experimental and previous numerical results.